Synthesis, Antifungal Activity, and Molecular Docking Studies of Some New Di-OIsopentanoyl Glucopyranosides - Priyanka, Matin; Mohammed Mahbubul, Matin; Md. Rezaur, Rahman; A., Kumer (Iranian Chemical Society, 2023)
Extensive research over the past decades has shown that sugar ester (SE)-type biomolecules bring long-chain fatty acids with sugar moieties into the plant cells and play various important roles in food, surfactants, innovative green materials, and biological properties. Thus, in this study, dimolar isopentanoylation of methyl α-D-glucopyranoside (compound 4) furnished methyl-2,6-di-O-isopentanoyl-α-Dglucopyranoside (compound 5), indicating selectivity at C-2 and C-6 positions. The obtained compound (5) was further acylated to give 3,4-di-O-acyl esters (compounds 5-8) in good yields. In vitro antifungal activities of these compounds exhibited moderate to good zone of inhibition. To rationalize these results, molecular docking studies of compounds 4-8 were performed on lanosterol 14-α-demethylase (CYP 51). The attachment of acyl ester chain(s) to the glucopyranoside ring added more lipophilicity and affected their fungal inhibition by binding to the lanosterol 14-α-demethylase enzyme. In particular, the isopentanoyl group showed a stronger binding affinity with lauroyl groups, as in compound 8, than with the fluconazole group, indicating the higher efficiency of SEs.